Prostaglandin E2 stimulates opposing effects on inner and outer blood-retina barrier function - Stark, Amy K.; Gilmartin, Anna R.; Ontko, Cayla D.; Smith, Taylor E.; Beall, Amanda L.; McCollum, Gary W.; Penn, John S. (Frontiers in Pharmacology, 2025)
IntroductionDiabetic retinopathy (DR) is the leading cause of vision loss in working-age individuals globally, and the associated complication of diabetic macular edema (DME) is the most frequent cause of vision loss in these patients. The retinal swelling characteristic of DME can be attributed to fluid leakage due to damage to the two blood-retina barriers—the inner barrier composed primarily of retinal microvascular endothelial cells and the outer barrier composed of retinal pigment epithelial cells (RPE).MethodsBased on the previously characterized proinflammatory roles of prostanoid signaling in DR, we assayed the distinct prostanoid signaling mechanisms regulating inner and outer blood-retina barrier function using in vitro methods involving monoculture of primary human cells.ResultsProstaglandin E2 (PGE2) stimulation of retinal endothelial monolayers caused a decrease in barrier permeability in electric cell-substrate impedance sensing (ECIS) assays and dextran flux assays. These effects occurred via the EP4 receptor of PGE2. In direct contrast, PGE2 stimulation of RPE monolayers caused an increase in barrier permeability via the EP2 receptor. Other prostanoids did not alter barrier permeability in either monocellular model. RNA sequencing of retinal endothelial and RPE cells with or without PGE2 stimulation revealed significant dysregulation of genes encoding junctional complex components and signaling that likely drive the observed effects on cell barrier resistance.DiscussionTogether these results suggest opposing mechanisms of PGE2 signaling in the retina via two distinct receptors, indicating cell type-specific and likely receptor-specific targets for the potential therapeutic management of DME or other causes of dysfunctional retinal vascular permeability.